Corporate Criminal Liability Arrangements in the IUS Constituendum - Mohammad Fajarudin (Eduvest - Journal of Universal Studies, 2021)
The development of science and technology and globalization were already unstoppable today, not only have a beneficial impact, but also often have a negative impact for example by the "globalization of crime" and the development of quality (modus of operation) and the quantity of criminal acts. Offenses rife nowadays with regard to the corporate existence of the corporation is a criminal offense that could result in serious and widespread impact, damage the joints of the nation and threatens the stability of the State. Therefore, the law should take back its role in order to create justice and welfare and in handling needed ways remarkable that one of them is to make the corporation as a subject of criminal law that is considered to be committing a crime and can be criminally).